Avaliação ecotoxicológica da adição de nitrato em sedimentos eutrofizados da Represa Ibirité (Betim MG): experimentos em microcosmos - Janke, Helena (Universidade Federal de São Carlos, 2009)
The objective of the present dissertation was to make a toxicity assessment of the application of calcium nitrate solution as a remediation procedure for sediments of a eutrophic aquatic ecosystem. The study was carried out using microcosms with superficial sediments and water from sediment-water interface of the Ibirité Reservoir located in the metropolitan area of Belo Horizonte (Minas Gerais, SE Brazil). The experiment lasted 135 days and the following treatment or incubation periods were applied: t=0, t=5, t=10, t=25, t=50, t=85 and t=135 days. In each period, one controlmicrocosm and three treatment-microcosms were disassembled and, chemically and ecotoxicologically analyzed. The organisms Ceriodaphnia silvestrii and Vibrio fischeri (Microtox® System) were used for the acute toxicity assessment of the water from sediment-water interface and the pore water of sediments, whereas the organism Chironomus xanthus was used for the toxicity assessment of bulk sediment. The toxicity tests were run in parallel with chemical analyzes of dissolved inorganic nitrogen species (nitrate, nitrate and ammonium), sulfate, and metals in the interface sediment-water and interstitial water samples. Acid volatile sulfide (AVS), simultaneously extracted metal (SEM) and potentially bioavailable metals were analyzed in bulk sediment. The overall results indicate that nitrate whose concentration reached 1,200 mg N-NO3 - L-1 in sediment pore water samples from treatment-microcosms is the most probable compound causing toxicity to the tests organisms. For Chironomus xanthus sediments were deleterious to the exposed organisms in all microcosm run, except in the period of t= 135 days. For the experimental conditions of this work, the application of calcium nitrate as a remediation procedure for sediments from Ibirité Reservoir indicated to be inadequate from the ecotoxicological pint of view.
Keywords: Ecologia; Ecotoxicologia; Sedimentos; Toxicidade - testes; Nitrato de cálcio; Microtox®; Chironomus xanthus; Vibrio fischeri; Ceriodaphnia silvestrii; Sediment remediation; Calcium nitrate; Acute toxicity; CIENCIAS BIOLOGICAS::ECOLOGIA